On the construction of samples for testing approximate optimization methods for estimate calculation algorithms - Dokukin, A. A. (Computational mathematics and mathematical physics, 2006)
To validate approximate optimization schemes for estimate calculation algorithms (ECAs), it is necessary to compute the optimal height, which cannot be done in a reasonable amount of time. A variety of samples are built for which the optimal height of the ECAs is known by construction.[PUBLICATION ABSTRACT]